The impact of flexible work policies on 'shadow work' and gender equality advocacy among female academics - Febrianty, Febrianty; Sentanu, I Gede Eko Putra Sri; Martini, Rita; Divianto, Divianto (Annals of Human Resource Management Research, 2025)
Purpose: Flexible work policies remote work, flexible schedules, and compressed workweeks are intended to improve work-life balance for female academics with added responsibilities. In Indonesia, despite alignment with labor laws, implementation remains inconsistent and overlooks gender bias and shadow work such as mentoring and administration. This study examines their impact on shadow work and gender equality advocacy, stressing institutional support. Methodology: This research employs a mixed-methods approach, integrating Structural Equation Modeling (SEM) Partial Least Squares (PLS) for quantitative analysis and thematic analysis using NVivo for qualitative insights. Data were collected through surveys from 450 female academics and in-depth interviews with 30 respondents from various universities. Results: Findings show that flexible work policies reduce shadow work but only strengthen gender equality advocacy when backed by strong institutional support. Policy intensity, not mere availability, drives advocacy, while weak structures leave female academics burdened with shadow work and limited advocacy roles. Conclusions: This study concludes that flexible work policies alone are insufficient to drive systemic change in gender equality within academia. Their effectiveness is highly dependent on institutional culture, leadership commitment, and policy integration into broader faculty development programs. Limitations: Stronger institutional support, policy refinement, and awareness campaigns are recommended to ensure that flexible work arrangements not only improve work-life balance but also empower female academics in advocacy and leadership roles. Contribution: Future research should explore the long-term effects of flexible work policies and the intersection of social, economic, and cultural factors in shaping gender equity in higher education.